198k views
4 votes
10.........................

10.........................-example-1
User Songs
by
5.2k points

1 Answer

1 vote

Hello!

The answer is:

a.
a^{(3)/(2)}bc^(2)

Why?

To simplify the expression, we need to transform the radical into a exponential form, then apply the exponential property.

Transforming radical to exponential form:


\sqrt[n]{x}=x^{(1)/(n)}\\√(x)=x^{(1)/(2) }

Power of a power property:


(a^(m))^(n)=a^(mn)\\\\(a^(m))^{(1)/(n)}=a^{(m)/(n)}

So,


\sqrt[4]{a^(6)b^(4)c^(8)}=(a^(6)b^(4)c^(8))^{(1)/(4)}\\\\(a^(6)b^(4)c^(8))^{(1)/(4)}=a^{(6)/(4)}b^{(4)/(4)}c^{(8)/(4)}\\\\a^{(6)/(4)}b^{(4)/(4)}c^{(8)/(4)}=a^{(3)/(2)}bc^(2)

Have a nice day!

User Grisumbras
by
5.8k points